SINICIZATION OF CHRISTIANITY - Doyle, G. Wright (Journal of Research for Christianity in China (JRCC), 2025)
For more than two centuries, Chinese and Western Protestants have been trying to find ways to contextualize the Christian message in China. They have followed various approaches. Some prefer the “accommodationist” program of Matteo Ricci. Liberal Protestants followed this path in the twentieth century with the “Indigenous Theology” movement. Some evangelicals have recently also favored this way of making Christianity more acceptable to Chinese.